Influence of Acceptance Commitment Therapy (ACT) on Quality of Life of Cancer Patients: Literature Review - Liana Pujiastuti; Erin Rika Herwina (Rifa'Institute, 2022)
Introduction: The International Agency for Research on Cancer (IARC) estimates that 1 in 5 men and 1 in 5 women in the world's population will develop cancer at some point in their lives. One in eight men and one in eleven women with cancer will die. Acceptance Commitment Therapy (ACT) is a therapy that can be used to change the negative behavior of cancer patients. Objective: The purpose of this study was to explore the effect of ACT on improving the quality of life in cancer patients. Methods: This research uses a literature review method. The sample consists of 4 journals sourced from the academic databases PubMed, Google Scholar and Elseiver. Result and Discussion: The results showed that ACT had an effect on improving the quality of life of cancer patients. ACT can be given in conjunction with other therapies such as psychoeducational therapy, CBT, AT, assertive group activities, family support and others. ACT is very beneficial for cancer patients, because ACT can improve health behavior and quality of life for patients. Conclusion: ACT has an effect on improving the quality of life. Suggestion Mental Hospital in collaboration with educational institutions to develop ACT as an alternative therapy to improve the quality of life in cancer patients.